Let us go up to Zion : essays in honour of H.G.M. Williamson on the occasion of his sixty-fifth birthday - Williamson, H. G. M. 1947-; Provan, Iain W. 1957-; Boda, Mark J. (Vetus Testamentum, Supplements, 2012)
This volume honours Professor H. G. M. Williamson, Regius Professor of Hebrew at Oxford University through a collection of essays by colleagues and former students from across the globe. The various contributions intersect with the previous work of Professor Williamson, with special emphasis on the history of biblical research, study of the Hebrew language and Hebrew textual traditions, post-exilic historiography (Chronicles, Ezra-Nehemiah) and the prophets (especially Isaiah).